International Negotiation in the Council of the European Union - Marián Belko (Czech Journal of International Relations, 2009)
Negotiation is an important part of international relations when it covers the interaction among the states as its actors. Basically, we distinguish distributive bargaining and integrative problem-solving as two main approaches (or sets of strategies) in negotiation. Problem-solving seems to be more valuable in recognizing more effective solutions, but at the same time it is harder to adopt it. The main goal of this article is to find out which approach is typical for negotiation between member states of the European Union. By identifying the key determinants (level of politicization, nature of the question under negotiation, influence of sub-national and supranational actors, and interest cleavage) for the decision on the selection of an appropriate strategy, we argue that the context of the EU negotiation enables the identification of integrative solutions in a sufficient way.